Comparison Of Satellite-Correlated Crowdsourced And Geostatistical Temperature Projections For An Atlanta Heatwave Daily Snapshot: How Differences In Spatially-Variable Predictions May Be Correlated To Economic Status And Land Cover/Land Use. (2022) - Roberts, Allen D.
Abstract: This study was an endeavor to compare crowdsourced-based and geostatistical modeled projected temperature within the City of Atlanta during a September 2019 snapshot tied to a heat event. This study also ventured to decipher how spatially-variable discrepancies of prediction may be correlated to economic status via zip code and land cover/land use (LC/LU). Results suggests that satellite-correlated crowdsourced and geostatistical simulated temperature in the City of Atlanta during this snapshot to decipher differences in the spatial variations of forecasts may be correlated to economic status and LC/LU and can be implemented to potentially help with urban heat management strategies.